1996
DOI: 10.1104/pp.110.3.957
|View full text |Cite
|
Sign up to set email alerts
|

Fusicoccin Binding to Its Plasma Membrane Receptor and the Activation of the Plasma Membrane H+-ATPase (III. Is There a Direct Interaction between the Fusicoccin Receptor and the Plasma Membrane H+-ATPase?)

Abstract: A radioimmunoassay using antibodies raised against bovine serum albumin-conjugated fusicoccin (FC) was applied to measure FC bound to the plasma membrane (PM) isolated from seedlings of radish (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 39 publications
3
14
1
Order By: Relevance
“…The evidence presented here is supported by biochemical data on cosedimentation of H +-ATPase and fusicoccin binding activity (Cocucci and Marrè, 1991), copurification of the H+-ATPase and 14-3-3 protein that is abolished by trypsin treatment (Oecking et al, 1997), and recent data of De Michelis et al (1996). Using antibodies specific to fusicoccin, De Michelis et al (1996) showed a linear correlation between the amount of fusicoccin bound to the plasma membrane and activation of the H+-ATPase and suggested that no amplification step was needed but that activation of H+ pumping could be explained by direct interaction between the 14-3-3 protein and the H+-ATPase.…”
Section: Discussionsupporting
confidence: 83%
“…The evidence presented here is supported by biochemical data on cosedimentation of H +-ATPase and fusicoccin binding activity (Cocucci and Marrè, 1991), copurification of the H+-ATPase and 14-3-3 protein that is abolished by trypsin treatment (Oecking et al, 1997), and recent data of De Michelis et al (1996). Using antibodies specific to fusicoccin, De Michelis et al (1996) showed a linear correlation between the amount of fusicoccin bound to the plasma membrane and activation of the H+-ATPase and suggested that no amplification step was needed but that activation of H+ pumping could be explained by direct interaction between the 14-3-3 protein and the H+-ATPase.…”
Section: Discussionsupporting
confidence: 83%
“…PM fractions were separated from microsomal preparations by partitioning in an aqueous polymer two-phase system, as described previously (De Michelis et al, 1996). The upper (PM) phase as well as the lower phase were used for immunoblot analysis.…”
Section: Density Gradient Fractionation Of Membrane Vesiclesmentioning
confidence: 99%
“…In fact, it has been demonstrated that FC in vivo treatment of plant tissues, which produces a strong stimulation of H ϩ -ATPase activity, concomitantly brings about a marked increase in plasma membraneassociated 14-3-3 proteins (4,11). Also, the amount of FC bound to plasma membrane appears to be strictly correlated with stimulation of H ϩ -ATPase activity (12). More recent evidence indicates that administration of FC in vivo or in vitro stabilizes (13) or promotes (14) the interaction between H ϩ -ATPase and 14-3-3 proteins.…”
mentioning
confidence: 99%